Development of Crispy Brownies Enriched with Mung Bean Flour and Spinach Flour as an Alternative Snack for Pregnant Women - Faiza An Nabila; Rina Martini; Hadi Riyadi (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Protein and iron intake play an essential role in supporting fetal growth and development during pregnancy. Adequate protein intake helps reduce the risk of stunting and chronic energy deficiency (CED) among pregnant women. Crispy Brownies (Crispy Brownies) is a processed food product that can serve as an alternative snack for pregnant women. This study aimed to develop crispy brownies enriched with mung bean flour and spinach flour as an alternative snack, particularly for pregnant women with indications of chronic energy deficiency (CED) and anemia. The study was conducted through a series of product development stages, including nutrient composition analysis, nutritional adequacy assessment, and production cost analysis using three formulations (F1, F2, and F3). The results showed that formulation F2 (60% mung bean flour : 20% spinach flour) was the most preferred by the panelists, providing 535 kcal energy; 8.68 g protein; 30.7 g fat; 56.1 g carbohydrates; and 8.16 mg iron per 100 g. This product has the potential to serve as an iron-rich, protein-containing alternative snack for pregnant women as well as the general population.